(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Dermatoglyphics is a field of study that focuses on the patterns of ridges on the skin’s surface found on the palms of hands, fingers, and soles of the feet. During development, various creases develop on the brain and are reflected on fingerprints representing various regions of the brain and are commonly being used in dermatoglyphics mental intelligence test. It has been suggested that there is a relationship between dermatoglyphic patterns and various types of intelligence in humans. This study aims to investigate the potential correlation between intelligence level in young individual and dermal ridge pattern. Materials and methods: This study was conducted in the Department of Anatomy, Chattagram Maa-O-Shishu Hospital Medical College from November 2021 to May 2022. Sample were collected from Chattagram Maa-O-Shishu Hospital Medical College. Self-evaluating questionnaire was applied on 95 M.B.B.S. students of Phase I. The subjects were categorized into two groups- Category A including subjects with EQ>120 and Category B including subjects with EQ<120. Then the responses had entered as data into the Statistical Package for Social Science (SPSS) version 20 and data was analyzed using chi square test. Results: The Loop pattern has the highest incidence with a count of (n= 51). Additionally, it appears that students with the Loop pattern tend to score high on EQ (Emotional Quotient) tests, specifically scoring above 120. On the other hand, the Arch pattern has the lowest incidence rate with (n=21) and tends to have the lowest EQ scores, scoring below 120. The data is said to bear no statistical significance except L3 and L5 fingers with pvalues (0.02) in both that are statistically significant. 17% of total population scored EQ>120 and 83% population scored EQ <120 out of 150 total score. Conclusion The findings presented indicate a correlation between fingerprint patterns and emotional intelligence. This suggests that dermatoglyphics can be utilized as a tool to identify students who may have lower emotional intelligence and tailor teaching and counseling strategies accordingly. Some parents have started analyzing their children’ fingerprints in early age to understand their innate characters and learning potential in terms of personal, educational, or for preference in any other enterprise. JCMCTA 2023 ; 34 (1) : 90-94